Inflammatory myofibroblastic tumors in children: a single-center retrospective study of clinical features, management, and outcomes - Guo, FeiYue; Cui, QiangQiang; Lei, Yang; Xi, HongWei (Frontiers in Pediatrics, 2025)
BackgroundInflammatory myofibroblastic tumor (IMT) is a rare mesenchymal neoplasm of intermediate malignant potential. While its clinicopathologic features have been described in adults, comprehensive data in the pediatric population remain limited.MethodsWe retrospectively reviewed pediatric patients diagnosed with IMT at Shanxi Provincial Children's Hospital between January 2016 and June 2024. Clinical data, imaging, histopathology, immunohistochemistry (IHC), and outcomes were systematically analyzed.ResultsA total of 16 patients with complete clinical data and follow-up information were included. There were 10 male and 6 female patients, with a median age of 5.0 years. The primary tumor locations and clinical manifestations were diverse: 8 cases were located in the abdominal and pelvic cavities, presenting with abdominal pain, nausea, vomiting, and fever; 4 cases were located in the head, neck, and facial region, with 3 presenting as painless localized masses and 1 with inspiratory dyspnea; 1 case each occurred in the chest wall, gluteal region, and left upper limb, all presenting with painless localized masses; and 1 case occurred in the lung, presenting with cough, sputum, and recurrent respiratory infections. All 16 patients underwent surgery; three developed local recurrence requiring re-operation. At last follow-up, 15 were disease-free and one remained stable on ALK-targeted therapy.ConclusionPediatric IMT is a rare, low-grade malignancy with favorable prognosis. Complete surgical resection remains the cornerstone of treatment. ALK-targeted therapy may benefit patients with unresectable or recurrent disease. Long-term surveillance is warranted due to the risk of recurrence.